2020
DOI: 10.1111/1750-3841.15027
|View full text |Cite
|
Sign up to set email alerts
|

High pressure‐assisted vacuum‐freeze drying: A novel, efficient way to accelerate moisture migration in shrimp processing

Abstract: High pressure processing (HPP), as nonthermal processing technology, has the potential to increase the drying rate due to its improvement of heat and mass exchange in different processes. In this study, the moisture migration in shrimps during HPP‐vacuum‐freeze drying (HPP‐VFD) processes has been monitored by using low‐field nuclear magnetic resonance and magnetic resonance image (MRI) in comparison with hot air‐drying and VFD. Based on the T2 relaxation spectra, three water fractions corresponding to bound wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The effect of different drying methods on the migration of entrapped water in tilapia fillets ((a) the peak area of the entrapped water; b: the ratio of the entrapped water to the total peak area; (a) UAPOHPD; (b) UAPOVFHPCD) to 44.5℃ at 7 hr of drying from Figure 7a, and the entire sample temperature from surface to the temperature inside the sample reached about 45°C. There is a peak at this temperature, and it might be due to the entire muscle fiber network of the tilapia fillets tend to shrink and break, which increases the content of the free water (Ling et al, 2020); therefore, it can be assumed that the peak of the free water curves is represented as cell membrane collapse point. However, when the drying time was greater than 7 hr, the center temperature and surface temperature of the samples were the same, and the remaining free water in the samples continuously diffused into the drying medium, resulting in a decreasing trend.…”
Section: Lf-nmr Spectra Of Tilapia Fillets Under Different Drying Conditionsmentioning
confidence: 99%
“…The effect of different drying methods on the migration of entrapped water in tilapia fillets ((a) the peak area of the entrapped water; b: the ratio of the entrapped water to the total peak area; (a) UAPOHPD; (b) UAPOVFHPCD) to 44.5℃ at 7 hr of drying from Figure 7a, and the entire sample temperature from surface to the temperature inside the sample reached about 45°C. There is a peak at this temperature, and it might be due to the entire muscle fiber network of the tilapia fillets tend to shrink and break, which increases the content of the free water (Ling et al, 2020); therefore, it can be assumed that the peak of the free water curves is represented as cell membrane collapse point. However, when the drying time was greater than 7 hr, the center temperature and surface temperature of the samples were the same, and the remaining free water in the samples continuously diffused into the drying medium, resulting in a decreasing trend.…”
Section: Lf-nmr Spectra Of Tilapia Fillets Under Different Drying Conditionsmentioning
confidence: 99%
“…Levels of TBARS in HPP samples were greatly increased (up to 0.93 ± 0.09 mg MDA/kg at 400 MPa for 10 min) which was caused by the formation of hydroperoxides during HPP treatment. traditional thermal methods are available for microbiological inactivation, HPP is a time-saving and energy-efficient preservation technique for the seafood industry for opening shellfish or crustaceans (Ling et al, 2020). Using HPP , the bivalve shells opened with ease and allowed efficient meat extraction without affecting the product while avoiding cooking.…”
Section: Quality and Safety Of Hpp-treated Shellfishmentioning
confidence: 99%
“…The authors also noted the strong anti-inflammatory effect of freeze-dried ginseng when the combination of UVT and HHP was used. A previous study [73] used HHP for shrimp pretreatment before FD. The authors of the study observed that HHP improved drying efficiency and moisture migration from the exterior to the interior part of shrimp.…”
Section: High Hydrostatic Pressurementioning
confidence: 99%